FRANK WOOD'S BUSINESS ACCOUNTING : An Introduction to Financial Accounting - Sangster, Alan; Gordon, Lewis (Lecturer in accounting); Wood, Frank, 1926-2000 (Pearson, 2021)
"This edition marks a major change in focus that reflects the consolidation of the previous two volumes into one. The emphasis is now exclusively on financial accounting. This change, and the resulting increased focus on company accounting and International GAAP within the text, were made in response to the comments of reviewers of the previous edition, who felt this was what we should be focusing on. This textbook has been written to provide a very thorough introduction to accounting. Anyone seeking to obtain a good grounding in financial accounting will find this book suitable to their needs. This includes those studying accounting on courses at school, college or university; or studying for qualifications from the LCCI, Association of Accounting Technicians, the Institute of Secretaries and Administrators; or for qualifications of any of the six UK and Irish Chartered Accountancy bodies. The financial accounting requirements for National Vocational Qualifications and Scottish Vocational Qualifications are also fully covered"--